INDONESIAN SYNTACTIC INTERFERENCE IN ENGLISH ESSAYS OF ENGLISH EDUCATION PROGRAM STUDENTS FACULTY OF EDUCATION AND TEACHER TRAINING UMSU - Niswa, Khairun; Lubis, Bambang Nur Alamsyah; Srikandi, Cut Novita; Saragih, Mandra (Jurnal As-Salam, 2023)
In formal educational institutions, mastering English as a second language is a must, especially for students majoring in English. Language mastery often poses challenges because each language has different elements. Proficiency in a foreign language such as English involves mastering four language skills, including writing essays. This study presents research results regarding Indonesian syntactic interference in English essays. This study used a descriptive qualitative method. The analysis begins by reviewing all available data from respondents, and the steps are 1) Collecting exam data, 2) Identifying errors due to syntactic interference, 3) Classifying errors according to indicators of syntactic interference, and 4) Explaining student errors in English essays. Research findings show that, although many students can write English essays with correct grammar, students, especially in their fourth semester at FKIP UMSU, still show the influence of Indonesian in the sentence structure of their English essays.